2011
DOI: 10.1007/s12598-011-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel nanoporous palladium catalyst for formaldehyde electro-oxidation in alkaline media

Abstract: In this work palladium nanoparticles (nanoPd) were successfully fabricated using a hydrothermal method from the solution of PdCl 2 + EDTA + HCHO. SEM image of the nanoPd exhibits a novel three-dimensional porous texture, presenting high stability and significantly large real surface area. Electrocatalytic activity of the nanoPd towards formaldehyde oxidation in alkaline media was evaluated by cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS). Electrooxidation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The peak potentials for the oxidation of formaldehyde (Figure d) are at −0.24 V in the forward scan and at −0.34 V in the reverse scan. The oxidation current in the forward scan is due to the oxidation of formaldehyde into formic acid, which is further oxidized into carbon di/mono-oxide, contributing to the oxidation current in the reverse scan. The ratio of ( I p,f / I p,r ) formaldehyde and Q formaldehyde were estimated to be 0.93 and 18.4 μC, respectively. Control experiments show that no oxidation of those four liquid fuels was realized on either a bare glassy carbon electrode or the CNTs coated electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The peak potentials for the oxidation of formaldehyde (Figure d) are at −0.24 V in the forward scan and at −0.34 V in the reverse scan. The oxidation current in the forward scan is due to the oxidation of formaldehyde into formic acid, which is further oxidized into carbon di/mono-oxide, contributing to the oxidation current in the reverse scan. The ratio of ( I p,f / I p,r ) formaldehyde and Q formaldehyde were estimated to be 0.93 and 18.4 μC, respectively. Control experiments show that no oxidation of those four liquid fuels was realized on either a bare glassy carbon electrode or the CNTs coated electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Literature review exhibits that important attention has been engrossed in the electro-oxidation of HCHO for many years [4,[7][8][9][10][11]. Various components have been used for the HCHO electro-oxidation containing Pd electrode [12], Pt nanoparticles/GCE [13], Pt electrode [14], Pt-MnO 2 [15], Cu electrode [6], Cu-Pd [3], Cu/Pd/MWCNTs/CPE [16], Pt-Pd/CNT [17], Au nanoparticles [18], rGO/ZnO composite [19], nickel phosphate/GCE [5], Ni-Pd/GCE [20], nickel phosphate/carbon composite [21], Ni thin lm on SiO 2 /Au [22], Ni(OH) 2 -Pt/Al 2 O 3 [23], Ni(OH) 2 -MIL/CPE [24] and zeolite-modi ed electrodes containing Ni(OH) 2 [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 These materials have caught great scientic and technological interests. [12][13][14][15] Recently, the graphene sheets functionalized with metal nanoparticles had shown to increase the selectivity, sensitivity, limit of detection, response, or an unio of these performances. [16][17][18][19] Gutés et al 16 exploited an simple and easy-to-implement method of electroless deposition of Au nanoparticles to fabricate Au-decorated graphene sensor for H 2 S detecting in relatively fast response.…”
Section: Introductionmentioning
confidence: 99%
“…It had demonstrated that palladium nanoparticles could be the very effective oxidation catalysts and electrochemical sensors for formaldehyde. 12,13,[20][21][22][23] The formaldehyde detecting properties of single-walled carbon nanotube hybridized with Pd were investigated by density-functional theory calculations. 22 These researches indicated that metal nanoparticles decorated graphene shows a great potential for applying to the gas sensing and catalysis.…”
Section: Introductionmentioning
confidence: 99%